Risk propensity in the foreign direct investment location decision of emerging multinationals - Buckley, Peter J; Chen, Liang; Clegg, L Jeremy; Voss, Hinrich (Journal of International Business Studies, 2018)
A distinguishing feature of emerging economy multinationals is their apparent tolerance for host country institutional risk. Employing behavioral decision theory and quasi-experimental data, we find that managers’ domestic experience satisfaction increases their relative risk propensity regarding controllable risk (legally protectable loss), but decreases their tendency to accept noncontrollable risk (e.g., political instability). In contrast, firms’ potential slack reduces relative risk propensity regarding controllable risk, yet amplifies the tendency to take noncontrollable risk. We suggest that these counterbalancing effects might help explain prior ambiguous findings on the relationship between experience, slack, and FDI decisions. The study provides a new understanding of why firms exhibit heterogeneous responses to host country risks, and the varying effects of institutions.